Effects of treadmill running and fatigue on impact acceleration in distance running - Garcia-Perez, J. A.; Perez-Soriano, P.; Llana Belloch, A.; Lucas-Cuevas, A. G.; Sanchez-Zuriaga, D. (Sports Biomechanics, 2014)
The effects of treadmill running on impact acceleration were examined together with the interaction between running surface and runner's fatigue state. Twenty recreational runners (11 men and 9 women) ran overground and on a treadmill (at 4.0 m/s) before and after a fatigue protocol consisting of a 30-minute run at 85% of individual maximal aerobic speed. Impact accelerations were analysed using two lightweight capacitive uniaxial accelerometers. A two-way repeated-measure analysis of variance showed that, in the pre-fatigue condition, the treadmill running decreased head and tibial peak impact accelerations and impact rates (the rate of change of acceleration), but no significant difference was observed between the two surfaces in shock attenuation. There was no significant difference in acceleration parameters between the two surfaces in the post-fatigue condition. There was a significant interaction between surface (treadmill and overground) and fatigue state (pre-fatigue and post-fatigue). In particular, fatigue when running overground decreased impact acceleration severity, but it had no such effect when running on the treadmill. The effects of treadmill running and the interaction need to be taken into account when interpreting the results of studies that use a treadmill in their experimental protocols, and when prescribing physical exercise.